Clean-label breadmaking: Size exclusion HPLC analysis of proteins in dough supplemented with additives vs hard red spring wheat flour. (March 2022) - Rahman, Md Mahfuzur; Ohm, Jae‐Bom; Simsek, Senay
Abstract: Currently, there is a challenge for clean-label bread formulations to find replacements for dough improvers. For pan bread traditionally made from hard winter wheat, the addition of hard spring wheat flour may be an option to replace some dough improvers. Protein composition and properties of hard red spring wheat dough that would improve the quality of winter wheat dough for the purpose of replacing dough improvers need to be investigated. Therefore, this research aimed to compare molecular weight distribution (MWD) of unreduced proteins in dough samples that were made of a base hard red winter wheat flour supplemented with hard red spring (HRS) wheat flour or common additives such as potassium bromate, azodicarbonamide, ascorbic acid, sodium stearoyl lactylate, vital wheat gluten, non-fat dry milk, and others. The incorporation of the artificial additives significantly ( p  < .05) increased the quantity of total high molecular weight protein polymers (HMW-PP) in base-flour dough samples, which led to the improvement of breadmaking quality. Nonetheless, the HRS wheat flour naturally contained better protein quantity and quality, which sequentially contributed to forming more HMW-PP and a stronger gluten network in the dough than the base flour dough containing artificial additives. This research reported novel information on the variation of protein MWD in dough samples, especially those supplemented with artificial additives. The results support that the HRS wheat flour is an adequate choice as a blending flour to produce a clean-label bread substituting artificial additives. Graphical abstract: Image 1 Highlights: Additives increased total HMW polymeric proteins in winter wheat (WW) dough. Improved WW bread quality may be related to increased HMW polymeric proteins. Hard red spring (HRS) flour had higher HMW polymeric protein without additives. HRS dough formed a stronger gluten network than WW dough containing additives. HRS flour is an adequate choice as a blending flour to produce a clean-label bread.